Progress and prospects of long noncoding RNAs in lipid homeostasis - Zheng Chen (Elsevier, 2016)
Background: Long noncoding RNAs (lncRNAs) are a novel group of universally present, non-coding RNAs (>200 nt) that are increasingly recognized as key regulators of many physiological and pathological processes. Scope of review: Recent publications have shown that lncRNAs influence lipid homeostasis by controlling lipid metabolism in the liver and by regulating adipogenesis. lncRNAs control lipid metabolism-related gene expression by either base-pairing with RNA and DNA or by binding to proteins. Major conclusions: The recent advances and future prospects in understanding the roles of lncRNAs in lipid homeostasis are discussed. Keywords: lncRNA, Liver, Lipid metabolism, Adipose tissue, Adipogenesis